Globalization comes to the rescue: How dependency makes us more resilient - Oscar Guinea; Florian Forsthuber (European Centre for International Political Economy (ECIPE), 2020)
A new consensus is growing across the European Union - and other parts of the world too: that globalization has gone too far. The argument goes as follows: as an exchange for higher efficiency and lower prices, Europe has sacrificed its ability to take care of itself and protect its own citizens. The Covid-19 crisis has revealed how much Europe depends on the rest of the world for products like medical goods and medicines. Therefore, if Europe does not want to live through another shortage of essential supplies, the lesson of the Covid-19 crisis is that the EU has to produce these products itself. This conclusion may sound intuitive but it is fundamentally wrong. Europe is not overly dependent on the rest of the world because most trade in the EU is done within its own borders. New evidence presented in this paper shows that there were only 112 products, making just 1.2% of the value of EU total imports, for which the four largest suppliers were non-EU countries as compared to more than two thousand products for which the four largest suppliers were from EU member states. And while not every product is equally important in the face of a global pandemic, there is not a single Covid-19 related good for which all EU imports only came from non-EU countries. This paper debunks the idea that the EU is too reliant on other countries. Instead, our analysis shows that imports from the rest of the world make every EU member state more resilient by diversifying its sources of supply.
Keywords: 330; Globalisierung; Auslandsverlagerung; Coronavirus; Nationale Sicherheit; Diversifikation; Coping-Strategie; EU-Staaten